A finite-time-convergent composite guidance law with strong fault-tolerant performance. (July 2019) - Chen, Feng; He, Guangjun; He, Qifang
To improve the performance of tracking and intercepting the low-altitude target, a nonlinear integral sliding mode guidance law is designed firstly, which can guarantee that the line-of-sight angle converges to a desired tracking angle and the line-of-sight angular rate converges to zero in finite time. Meanwhile, to solve the chattering problem caused by the high gain coefficient of the sign function in the guidance law, a sliding mode disturbance observer is designed to estimate the maneuvering acceleration of the target. Moreover, a composite nonlinear integral sliding mode guidance law is designed by introducing the estimated value of the acceleration, which can weaken the chattering phenomenon effectively. Finally, considering the magnitude loss fault of the guidance command that may occur in the practical implementation, a composite guidance law with strong fault-tolerant performance is designed by introducing a fault compensation command, which can effectively improve the reliability of the system.